Non‐malignant portal vein thrombosis in a cohort of cirrhotic patients: Incidence and risk factors. Issue 10 (17th August 2021) - Lopez‐Gomez, Marta; Llop, Elba; Puente, Angela; Hernández Conde, Marta; Ruiz, Patricia; Alvárez, Silvia; Martínez, Jose Luis; Abad, Javier; Fernández, Natalia; Perelló, Christie; Fernández‐Carrillo, Carlos; Ferre, Carlos; et al.
Abstract: Aim: Non‐malignant portal vein thrombosis (PVT) is a complication of liver cirrhosis. The aim of this study was to evaluate the annual incidence of PVT and related risk factors. Methods: We retrospectively reviewed clinical, laboratory, and radiological data collected prospectively from September 2016 to September 2017. A follow‐up of 36 months was performed in a subset of patients to determine the cumulative incidence of PVT and related complications. Results: The study included 567 patients. The incidence of PVT at 12, 24, and 36 months was 3.7%, 0.8%, and 1.4%, respectively. Patients with PVT were compared with patients without PVT, and showed differences in albumin ( p = 0.04), aspartate aminotransferase ( p = 0.04), hemoglobin ( p = 0.01), and prothrombin activity ( p = 0.01). The presence of hydropic decompensation (57.1% vs. 30.1%; p 0.004), gastroesophageal varices (76.2% vs. 39.5%; p = 0.05), variceal bleeding (52.4% vs. 22.7%; p < 0.001), hepatic encephalopathy (38.1% vs. 9.9%; p = 0.01), spontaneous bacterial peritonitis (9.5% vs. 1.7%; p < 0.001), and use of beta‐blockers (71.4% vs. 27.7%; p < 0.001) were significantly associated. In the multivariate analysis, use of beta‐blockers and hepatic encephalopathy appeared as risk factors, and high albumin levels a protective factor. Conclusions: The incidence of PVT was 3.7%. Beta‐blockers and hepatic encephalopathy were risks factors. High albumin levels were a protective factor.